Deep brain stimulation for the treatment of Alzheimer's disease: A systematic review and meta-analysis - Majdi, Alireza; Deng, Zhengdao; Sadigh-Eteghad, Saeed; De Vloo, Philippe; Nuttin, Bart; Mc Laughlin, Myles (Frontiers in Neuroscience, 2023)
Background One of the experimental neuromodulation techniques being researched for the treatment of Alzheimer's disease (AD) is deep brain stimulation (DBS). To evaluate the effectiveness of DBS in AD, we performed a systematic review and meta-analysis of the available evidence. Methods From the inception through December 2021, the following databases were searched: Medline via PubMed, Scopus, Embase, Cochrane Library, and Web of Science. The search phrases used were “Alzheimer's disease,” “AD,” “deep brain stimulation,” and “DBS.” The information from the included articles was gathered using a standardized data-collecting form. In the included papers, the Cochrane Collaboration methodology was used to evaluate the risk of bias. A fixed-effects model was used to conduct the meta-analysis. Results Only five distinct publications and 6 different comparisons (one study consisted of two phases) were included out of the initial 524 papers that were recruited. DBS had no impact on the cognitive ability in patients with AD [0.116 SMD, 95% confidence interval (CI), −0.236 to 0.469, p = 0.518]. The studies' overall heterogeneity was not significant (κ2 = 6.23, T2 = 0.053, df = 5, I2 = 19.76%, p = 0.284). According to subgroup analysis, the fornix-DBS did not improve cognitive function in patients with AD (0.145 SMD, 95%CI, −0.246 to 0.537, p = 0.467). Unfavorable neurological and non-neurological outcomes were also reported. Conclusion The inconsistencies and heterogeneity of the included publications in various target and age groups of a small number of AD patients were brought to light by this meta-analysis. To determine if DBS is useful in the treatment of AD, further studies with larger sample sizes and randomized, double-blinded, sham-controlled designs are required.